(untitled) (Higher Education Politics and Economics, 2026)
Studentification is a process of neighborhood change characterized by the in-migration of postsecondary students. While studentification is generally conceptualized in the literature as an organic process tied to shifts toward mass higher education participation, I argue universities are not powerless actors in development. They have some degree of control over student residential patterns through university-led urban development initiatives, known as anchor institution initiatives. Utilizing US decennial census data from 1970 to 2010, I employ an inverse probability weighting difference-in-differences model to estimate the effect of anchor initiatives on rates of studentification. Results show a positive effect on studentification in neighborhoods targeted by an anchor initiative. I also find a positive relationship between studentification and rent prices.